2013 Proceedings IEEE INFOCOM 2013
DOI: 10.1109/infcom.2013.6566843
|View full text |Cite
|
Sign up to set email alerts
|

An upper bound on the convergence time for quantized consensus

Abstract: We analyze a class of distributed quantized consensus algorithms for arbitrary networks. In the initial setting, each node in the network has an integer value. Nodes exchange their current estimate of the mean value in the network, and then update their estimation by communicating with their neighbors in a limited capacity channel in an asynchronous clock setting. Eventually, all nodes reach consensus with quantized precision. We start the analysis with a special case of a distributed binary voting algorithm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Using Theorem 2 in the last relation of (4), we obtain that the expected time until all walkers collapse to one big clump is of the order of at most O(n 2 log n). Finally, using the same argument as in Corollary 4 in [16] we can see that O(n 2 log n) is an upper bound for the expected convergence time of the quantized Metropolis dynamics.…”
Section: Theoremmentioning
confidence: 57%
See 1 more Smart Citation
“…Using Theorem 2 in the last relation of (4), we obtain that the expected time until all walkers collapse to one big clump is of the order of at most O(n 2 log n). Finally, using the same argument as in Corollary 4 in [16] we can see that O(n 2 log n) is an upper bound for the expected convergence time of the quantized Metropolis dynamics.…”
Section: Theoremmentioning
confidence: 57%
“…Moreover, an upper bound of O(n 2 m max D max log 2 n) on the expected convergence time of unbiased quantized consensus in the presence of connected time-varying networks has been given in [15], where m max and D max denote, respectively, the maximum number of edges and the maximum diameter in the sequences of time-varying networks. The biased quantized consensus problem was addressed in [16], where it was shown that the expected convergence time in general networks is at most O(n 3 log n). Moreover, a deterministic version of the quantized-consensus algorithm was introduced in [17], where the authors showed a fast convergence time of O(n 2 ) for such dynamics.…”
mentioning
confidence: 99%
“…As in [9] and [6], we define the potential function Φ(·, ·) : V × V → R to be Φ(x, y) = H Z (x, y) + H Z (y, w) − H Z (w, y). Now consider the original joint process for two walkers on a finite graph.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Since by definitionT (G) is independent of the initial states of walkers, max x,y M (x, y) ≤ T (G). For the upper bound, we use the same argument used in [6]. Indeed half of the time when two walkers meet in the virtual process, they do not meet in the original process and they stay in the same position.…”
Section: X) (13)mentioning
confidence: 99%
See 1 more Smart Citation